Photophysical investigation of light-harvesting systems for solar-to-fuel conversion - Gullo, Maria Pia <1987> (Alma Mater Studiorum - Università di Bologna, 2015)
In recent years, an increasing attention has been given to the optimization of the performances of new supramolecular systems, as antennas for light collection. In such background, the aim of this thesis was the study of multichromophoric architectures capable of performing such basic action. A synthetic antenna should consist of a structure with large UV-Vis absorption cross-section, panchromatic absorption, fixed orientation of the components and suitable energy gradients between them, in order to funnel absorbed energy towards a specific site, through fast energy-transfer processes. Among the systems investigated in this thesis, three suitable classes of compounds can be identified: 1) transition metal-based multichromophoric arrays, as models for antenna construction, 2) free-base trans-A2B-phenylcorroles, as self-assembling systems to make effective mimics of the photosynthetic system, and 3) a natural harvester, the Photosystem I, immobilized on the photoanode of a solar-to-fuel conversion device. The discussion starts with the description of the photophysical properties of dinuclear quinonoid organometallic systems, able to fulfil some of the above mentioned absorption requirements, displaying in some cases panchromatic absorption. The investigation is extended to the efficient energy transfer processes occurring in supramolecular architectures, suitably organized around rigid organic scaffolds, such as spiro-bifluorene and triptycene. Furthermore, the photophysical characterization of three trans-A2B-phenylcorroles with different substituents on the meso-phenyl ring is introduced, revealing the tendency of such macrocycles to self-organize into dimers, by mimicking natural self-aggregates antenna systems. In the end, the photophysical analysis moved towards the natural super-complex PSI-LHCI, immobilized on the hematite surface of the photoanode of a bio-hybrid dye-sensitized solar cell. The importance of the entire work is related to the need for a deep understanding of the energy transfer mechanisms occurring in supramolecules, to gain insights and improve the strategies for governing the directionality of the energy flow in the construction of well-performing antenna systems.